Dabigatran use in Danish atrial fibrillation patients in 2011: a nationwide study. Issue 5 (3rd May 2013) - Sørensen, Rikke; Gislason, Gunnar; Torp-Pedersen, Christian; Olesen, Jonas Bjerring; Fosbøl, Emil L; Hvidtfeldt, Morten W; Karasoy, Deniz; Lamberts, Morten; Charlot, Mette; Køber, Lars; Weeke, Peter; Lip, Gregory Y H; et al.
Abstract : Objective: Dabigatran was recently approved for anticoagulation in patients with atrial fibrillation (AF); data regarding real-world use, comparative effectiveness and safety are sparse. Design: Pharmacoepidemiological cohort study. Methods/settings: From nationwide registers, we identified patients with an in-hospital or outpatient-clinic AF diagnosis who claimed a prescription of dabigatran 110 or 150 mg, or vitamin K antagonist (VKA), between 22 August and 31 December 2011. HRs of thromboembolic events (ischaemic stroke, transitory ischaemic attack and peripheral artery embolism) and bleedings were estimated using Cox regression analyses in all patients and stratified by previous VKA use. Results: Overall, 1612 (3.1%) and 1114 (2.1%) patients claimed a prescription of dabigatran 110 and 150 mg, and 49640 (94.8%) of VKA. Patients treated with dabigatran 150 mg were younger with less comorbidity than those treated with dabigatran 110 mg and VKA, as were VKA naïve patients compared with previous VKA users. Recommendations set by the European Medicine Agency (EMA) for dabigatran were met in 90.3% and 55.5% of patients treated with 110 and 150 mg. Patients treated with 150 mg dabigatran, who did not fulfil the recommendations by EMA, were >80 years, patients with liver or kidney disease, patients with previous bleeding. Compared with VKA, the thromboembolic risk associated with dabigatran 110 and 150 mg was HR 3.52 (1.40 to 8.84) and 5.79 (1.81 to 18.56) in previous VKA users, and HR 0.95(0.47 to 1.91) and 1.14(0.60 to 2.16) in VKA naïve patients. Bleeding risk was increased in previous VKA users receiving dabigatran 110 mg, but not in patients with 150 mg dabigatran, nor in the VKA naïve users. Conclusions: Deviations from the recommended use of dabigatran were frequent among patients treated with 150 mg. With cautious interpretation, dabigatran use in VKA naïve patients seems safe. Increased risk of thromboembolism and bleeding with dabigatran among previous VKA users was unexpected and may reflect patient selection and 'drug switching' practices.